Investigation of PVRIG as a potential target of LRBA - Ültanır, Ecem Gonca. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2023., 2023)
Identifying novel T-cell co-inhibitors and the mechanism of their regulation is of great importance for the development of novel immune checkpoint blockade therapies. LRBA is a key surface trafficking regulator of CTLA-4, which is a crucial T-cell co- inhibitory receptor. LRBA maintains immune homeostasis and prevents autoimmunity by directing internalized CTLA-4 back to the cell surface and preventing its lysosomal degradation. To date, the role of LRBA in the regulation of other T-cell co- receptors besides CTLA-4 have not been identified. In previous studies in our laboratory, a novel T-cell co-inhibitory receptor, PVRIG was found to be significantly downregulated on the surface of LRBA knockout Jurkat T-cells. In this thesis, we aimed to investigate this finding in more detail to find out whether LRBA regulates PVRIG through similar mechanisms as it regulates CTLA- 4. To this end, we performed several co- immunoprecipitation experiments to investigate the physical interaction between endogenous PVRIG and LRBA proteins. In addition, we tried to understand whether LRBA could bind to PVRIG with its PH-BEACH domain, which is sufficient for CTLA-4 binding. We showed that the Flag-tagged PH-BEACH domain of LRBA co-immunoprecipitated with various constructs of PVRIG, including full length PVRIG, Tailless PVRIG, and TM-Tail PVRIG, all carrying c-Myc/His epitope tags. However, we could not fully confirm the specificity of these co-immunoprecipitation results. Therefore, there is a need for further investigation of the PVRIG and LRBA interaction using additional techniques. We also showed that PVRIG protein can undergo glycosylation, which may have implications on its overall function. This study adds valuable insights towards the regulation of PVRIG by LRBA.
Keywords: T cells -- Research.